(untitled) (Research, Society and Development, 2022)
Diabetes is a metabolic condition marked by persistent hyperglycemia. In recent years, several methods for measuring blood glucose have come into circulation, such as the self-monitoring of capillary blood glucose (AMGC), the continuous blood glucose monitoring system (SMCG) and the Flash Glucose Monitoring (MFG) system. The latter measures the glucose present in the interstitial fluid, providing glycemic patterns, these values ​​are stored in a software and assist in treatment changes to improve patients’ glycemic control. In the present study, we sought to compare glycemic indices in patients before using the MFG system, and after starting to use the technology. It was carried out through the collection of data from 14 patients in a doctor’s office, at the end of the research, a decrease in the values ​​of Glycated Hemoglobin and an improvement in the Target Glycemic Time was identified, increasing by 11% in patients with type Diabetes Mellitus 1 and 22% in patients with type 2. Through 2 case studies, it was identified in the patient who uses the method, but does not have healthy habits, that his results were not positive, presenting 32.2% of the time on target, while the patient who has healthy habits has 70% of the time on target. In this way, it was possible to conclude that the MFG provides positive impacts, but to have a better result, it must be correlated with healthy eating habits and physical exercise. However, further studies on the performance of the system are needed and the results presented are relevant for future comparisons.